THE USE OF NEW METHODS OF IN TEACHING INFORMATICS USNING BY ANDROID APPLICATIONS AND ARTIFICIAL INTELLIGENCE - Azamat Arslanbayevich Ismoilov (Web of Journals Publishing, 2024)
This article explores the application of artificial intelligence (AI) in teaching Information Technology (IT), highlighting its transformative impact on education. It examines AI's role in personalized learning, interactive environments, and skill-based training while discussing its advantages for students and educators. The article also addresses challenges such as ethical concerns, accessibility, and the need for teacher training. By analyzing current practices and future prospects, the study emphasizes AI's potential to enhance IT education and align it with the demands of the digital age.